Textile Muscle Fibers Made by and for Continuous Production Using Doped Conducting Polymers - Claude Huniade; Jose G. Martinez; Shayan Mehraeen; Edwin W. H. Jager; Tariq Bashir; Nils‐Krister Persson (Macromolecular Materials and Engineering)
Abstract Like skeletal muscles having a fibrous structure, conducting polymers can actuate upon electrical stimulation and can be shaped into fibers. Through textile assembly strategies of such fibers, complex actuating architectures are possible. However, state‐of‐the‐art strategies using short pieces of yarn, which compel manual integration, are not fully taking advantage of textiles. To manufacture actuating textiles that best exploit textile properties like softness and pliability, and to enable production upscaling, a production of continuous, actuating fibers is presented here. These fibers are produced from commercial polyamide 6/6 filaments by first continuously dip‐coating in a modified commercial poly(3,4−ethylenedioxythiophene):poly(styrene sulfonate) (PEDOT:PSS) dispersion before the electropolymerization of polypyrrole (PPy), where the fibers are withdrawn continuously through an electrolyte solution containing the pyrrole monomer. By employing a cyclic dip‐coating with individual viscosity, drying temperature, and withdrawal speed for each layer, and by adjusting the tension, speed, and applied potential of the electropolymerization, their isotonic strain is enhanced threefold. Their specific tension, at 400 µN tex−1, reaches slightly higher than human skeletal muscle fibers. Furthermore, these continuous actuating fibers produced on the meter are processable in an industrial knitting machine. This study anchors the development of textile muscle fibers for future textile muscles.